TRANSPARENCY INFORMED CONSENT RELATED TO PATIENT DISHONESTY AMID COVID-19 PANDEMIC IN INDONESIA: IN LAW PERSPECTIVE - Tiwuk Herawati; Fifik Wiryani; M. Nasser; Mokhammad Najih (Diponegoro Law Review, 2021)
To break the chain of transmission of covid-19 outbreak, the public is expected to be honest in explaining chronological physical contact when treating to health facilities, especially if the patient experiences symptoms of covid-19. Honesty of patients indicated by COVID-19 is very important so that the chain of transmission of covid-19 does not expand and facilitate health workers in data collection. Denial, lies, even like the refusal of covid-19 corpses if it continues to be left, does not mean the countermeasures of covid-19 are increasingly stretched. This article tries to review the transparency of informed consent in relation to patient dishonesty, where transparent communication is expected by the patient to be honest and not to cover the perceived symptoms or various things related to covid-19. This research is normative juridical research. In normative legal research, library material is the basic data that in research science is classified as secondary data.